2021
DOI: 10.23887/ijssb.v5i4.40446
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Electronic Archives as a Support for Study Employee Performance at The Customs and Excise Office Type A Semarang Customs

Abstract: Technological developments make it easier for employees to carry out work, including archive management employees. Archives undergo changes and developments in electronic form. The development of supporting technology for electronic archive management. This study aims to analyze the use of electronic records to support the effectiveness of employee performance and the factors that support employee performance. This qualitative research uses a descriptive approach. The technique used to collect data is intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Facilities and infrastructures provided to the employees play pivotal roles in determining the company's success. Adequate facilities and infrastructures will likely yield a performance according to the company's expectations (Abisuga et al, 2020;Dewi & Dewi, 2021). The research analyzes the effect of organizational commitment, emotional intelligence, and job satisfaction on employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…Facilities and infrastructures provided to the employees play pivotal roles in determining the company's success. Adequate facilities and infrastructures will likely yield a performance according to the company's expectations (Abisuga et al, 2020;Dewi & Dewi, 2021). The research analyzes the effect of organizational commitment, emotional intelligence, and job satisfaction on employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…The previous related study has been conducted by Dewi & Dewi (2021) and Saeroji et al (2021). Dewi & Dewi (2021) analyze the use of electronic records to support the effectiveness of employee performance and the factors that support employee performance. The results showed that the use of electronic archives supports employee performance.…”
Section: Introductionmentioning
confidence: 99%